2016
DOI: 10.1177/1088357616632446
|View full text |Cite
|
Sign up to set email alerts
|

Social Validity of Evidence-Based Practices and Emerging Interventions in Autism

Abstract: Although the field of autism intervention and treatment is still emerging, a lack of knowledge about what to do should no longer be considered a significant challenge facing service providers. Recent large-scale, systematic, and robust research reviews have identified interventions with strong empirical evidence of effectiveness in some outcome areas. The results of these reviews provide support for the use of specific treatments with individuals who have autism spectrum disorder (ASD), especially within certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…Additionally, this review highlights a lack of social validation. These results are consistent with other findings regarding lack of evidence of the measurement of social validation for EBPs for individuals with ASD (Callahan et al, 2016;Kennedy, 1992). Assessing social validity for self-monitoring interventions for adolescents with ASD is important because it will help determine the acceptability of procedures, outcomes, and goals from those directly affected by the intervention (Aladjeff-Abergel et al, 2015).…”
Section: Key Findings and Limitationssupporting
confidence: 92%
“…Additionally, this review highlights a lack of social validation. These results are consistent with other findings regarding lack of evidence of the measurement of social validation for EBPs for individuals with ASD (Callahan et al, 2016;Kennedy, 1992). Assessing social validity for self-monitoring interventions for adolescents with ASD is important because it will help determine the acceptability of procedures, outcomes, and goals from those directly affected by the intervention (Aladjeff-Abergel et al, 2015).…”
Section: Key Findings and Limitationssupporting
confidence: 92%
“…A possible explanation for the disconnection cited above is the perceived social validity of ESTs for education settings. 38,39 Social validity refers to the acceptability of the goals, procedures and outcomes of interventions. 40,41 As Greenway et al 42…”
Section: Social Validity As a Barrier To Est Uptakementioning
confidence: 99%
“…To better understand if interventions are meeting this indicator, acceptability should be measured in the intervention literature, though past reviews suggest it is infrequently reported (e.g., Villarreal, Ponce, & Gutierrez, ). This issue may be because a standardized approach to the assessment and reporting of acceptability continues to be absent from many applied research journal guidelines (Callahan et al, ; Roach, Wixson, Talapatra, & LaSalle, ) despite recommendations to include acceptability in professional practice and research. Without a standardized approach to the assessment and reporting of acceptability, it is unclear how practitioners and researchers report and interpret acceptability findings.…”
Section: Introductionmentioning
confidence: 99%